Surgical excision of skin folds from the head of a goldfish Carassius auratus (Linnaeus 1758) - ANGELIDIS (Π. ΑΓΓΕΛΙΔΗΣ) P.; VATSOS (Ι.Ν. ΒΑΤΣΟΣ) I. N.; KARAGIANNIS (Δ. ΚΑΡΑΓΙΑΝΝΗΣ) D. (Journal of the Hellenic Veterinary Medical Society, 2017)
Goldfish Oranda very often exhibit skin overgrown folds in the dorsal head area. In many cases, these folds extend laterally towards the periocular area resulting in tunnel vision and thus stress of the fish. A goldfish, about four years old, with overgrown skin folds around its eyes underwent a surgical excision of these folds. Prior to surgery and the last three consecutive days the fish was treated with the wide spectrum antibiotic nifurpirinol (Aquafuran) by bath. After the fish was anaesthetized with phenoxyethanol, the excessive skin folds were excised with a scalpel. Histological examination of the excised skin revealed hyperplasia of the epidermis and excessive subcutaneous fat tissue. During the first 24 hours after surgery the fish started to eat. In the next few days, its appetite and overall behaviour showed significant improvement compared to those prior to the operation, while almost 12 months post operation, no new skin folds appeared around the eyes, a fact that indicates that the operation improved the life of the fish.